The return response on gold and crude oil during global geopolitical issues - Azarya Putra Ari; Jordy Siwu; Merlyn Sari Sambur; Sisilia Kristiana Kawulur (The Contrarian : Finance, Accounting, and Business Research, 2023)
The geopolitical issues together with the COVID-19 pandemic in earlier of 2022 triggered instability in the world economy. The objective of this study is to analyze the correlation and response of the returns of firms in the energy sector to changes in gold and crude oil prices. The observed data is drawn over the period June 2021 to June 2022 on the monthly basis for 68 listed firms in the energy sector, gold prices, and crude oil prices. This study finds that the changes in gold returns tend not to affect the changes in returns of firms in the energy sector. Reversely, the changes in returns of crude oil significantly affect the changes in returns of firms in the energy sector.